Customer satisfaction towards services quality of public transportation in Kuching Area - Thian, Wan Jun (Universiti Malaysia Sarawak (UNIMAS), 2012)
This study examines customer satisfaction towards service quality of public transportation. Five dimensions in SERVQUAL were applied as the indicators to influence customer satisfaction. In this study determines that most significant elements that contribute to Service Quality Excellency. There are 200 set of questionnaire are distribute to the respondents and the response rate is 80% in this research. Data collected use in this research is descriptive statistic, Pearson correlation and multiple linear regressions. In this research, Pearson Correlation had shown that the five SERVQUAL dimensions having the positive relationship with the customer satisfaction. However, the mUltiple linear regressions is used to predict the impact of independent variable on the dependent variable. In other words, is to find out which one of the five dimensions in SERVQUAL is the best predictors of the customer satisfaction. In the nutshell, tangibility is most significant and more dominant in this research